The activity of avian rhodanese - Oh, S. Y.; Jalaludin, S.; Davis, R. H.; Sykes, A. H. (Taylor & Francis, 1977)
A survey of rhodanese activity (thiosulphate: cyanide sulphur transferase) in the tissues of the domestic fowl revealed that the highest activity occurred in the kidney, approximately twice that in the liver, 316 and 141 mumol SCN formed/min g protein, respectively. 2. In sparrows, pigeons and ducks, liver and kidney activities tended to be similar and increased with body size. 3. Relationships were found between enzyme activity and body weight to a fractional power, indicating relatively higher activity in smaller birds.